1991
DOI: 10.1111/j.1600-0404.1991.tb03964.x
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action of triethylenetetramine dihydrochloride on copper metabolism in Wilson's disease

Abstract: The drug of choice for the initial treatment of "decoppering" in Wilson's disease, an inherited disorder of copper metabolism, is the chelating agent D-penicillamine. In the case of harmful side-effects an alternative drug is triethylenetetramine dihydrocholoride (trien or trientine). Using the 24-h-urine excretion of copper and the oral copper loading test with copper-64, a double function for trien was found: trien increases the urine copper excretion and decreases the intestinal copper absorption respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 10 publications
1
25
0
1
Order By: Relevance
“…Values are means±SEM binding capacity, ferritin and numbers of white blood cells and platelets between baseline and 12 months did not differ significantly between treatment groups. Thus drug treatment tended to lower haemoglobin concentrations and erythrocyte numbers to a modest extent, in line with some previous reports [6]. Vigilance will be necessary in further studies of trientine treatment in patients at greater risk of haematological impairment, such as those with diabetic nephropathy [18].…”
Section: Concomitant Medicationssupporting
confidence: 64%
See 1 more Smart Citation
“…Values are means±SEM binding capacity, ferritin and numbers of white blood cells and platelets between baseline and 12 months did not differ significantly between treatment groups. Thus drug treatment tended to lower haemoglobin concentrations and erythrocyte numbers to a modest extent, in line with some previous reports [6]. Vigilance will be necessary in further studies of trientine treatment in patients at greater risk of haematological impairment, such as those with diabetic nephropathy [18].…”
Section: Concomitant Medicationssupporting
confidence: 64%
“…We recently characterised a hyperglycaemiadriven pathogenic abnormality of copper homeostasis in type 2 diabetic patients and showed that their Cu balance can be improved by treatment with trientine [5], a drug that is also sometimes used as a treatment for Wilson's disease [6]. Trientine also improves LVH, left ventricle (LV) function [7] and aortic structure [8] in rat models of diabetes, in which it also reverses cardiac fibrosis without altering blood glucose or BP.…”
Section: Introductionmentioning
confidence: 99%
“…However, the copper level of urine excreted after oral administration of TETA in the patients is unexpectedly low (Dubois et al 1970;Walshe 1973;Harders and Cohnen 1977;Haslam et al 1980;Saito et al 1991). Siegemund et al (1991) reported that the increase of copper level in the urine was 6.6±4.1,umol even when 1.2 g of TETA was orally administered. These findings along with the results of the present study and that of Kobayashi et al (1990) suggest that orally administered TETA in human is absorbed through the digestive tract, but that most of it is readily converted into a metabolite which loses its ability to chelate copper, and is then excreted into the urine.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical experience with TETA (in the form of trientine) has been predominantly limited to patients with Wilson's disease (1,16,(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67). The reported side effects are summarized in Table 3.…”
Section: Adverse Drug Reactions Toxicity and Safetymentioning
confidence: 99%
“…6, 15, 71). TETA not only increases urinary Cu excretion, but also decreases intestinal copper absorption by 80% (57). TETA and its metabolite, MAT, are both capable of binding divalent Cu, Fe, and Zn.…”
Section: Mechanism Of Action In Wilson's Diseasementioning
confidence: 99%